Comparative Study of Operative and Non-Operatively Treated Displaced Mid-Shaft Clavicle Fractures in Adults - Raja Adnan Ashraf, Muhammad Muneer Haider, Faizan Rauf, Hassan Iqbal, Rizwan Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A displaced mid-shaft clavicle fracture in an adult is a break in the collarbone, which is the long bone that runs from the shoulder to the chest. Mid-shaft fractures occur in the middle portion of the collarbone and the displaced fracture means that the broken pieces have moved out of their normal alignment. Study design: It is a comparative study conducted at Orthopedics Department of Pakistan Railway General Hospital, Rawalpindi for the duration of six months from Jan 2022 to June 2022. Material and Methods: The patients who were treated without operation were compared with operative patients for better results. Both groups contained 60 patients. The average age of the patients was 29.9±7.8 in the control group and 32.1±8.1 in the non-operative group. There were 32 and 28 patients in control group that had right and left side of injury respectively. This study was approved by the ethical and the review board committee of the hospital. The data was collected and statistical analysis was performed. Results: The functional outcome of the patients is constant score fracture was calculated and clavicle shortening was carefully observed. The average shortening of clavicle was 0.71±8.1 cm. After a follow-up of 3 months’ clavicle shortening was calculated. The outcome was linked to amount of clavicle shortening among patients Conclusion: The study was done to find the functional outcome of non-operatively treated displaced mid-shaft clavicle fractures in the adult as compared with the operatively treated patients. The results showed that non-operative management of minimally displaced mid shaft clavicle fracture also had good functional outcome. Keywords: Clavicle fracture and the non-operative treatment.